1981
DOI: 10.1007/bf00254494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of precursors on brain neurotransmitter synthesis and brain functions

Abstract: Abstract. This paper reviews factors which influence the levels of aminergic transmitters in the brain. In particular precursor availability to the brain influences the rates of synthesis of serotonin, the catecholamines, and acetylcholine by brain neurons. The diet readily influences brain neurotransmitter formation via this mechanism. At present, the importance of this relationship to body regulation is not well understood. Nonetheless, precursors (tryptophan, tyrosine, choline, and lecithin) have begun to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…The great change in appetite found among group A arsonists also supports the hypothesis that brain serotonin may be involved (41,42). Insulin regulates the amount of tryptophan to enter the brain and thus also the serotonin metabolism (43)(44)(45). It thus seems possible that a low brain serotonin level and enhanced insulin secretion are somehow connected with the reactive hypoglycemic condition among hypoglycemic arsonists.…”
Section: )mentioning
confidence: 55%
“…The great change in appetite found among group A arsonists also supports the hypothesis that brain serotonin may be involved (41,42). Insulin regulates the amount of tryptophan to enter the brain and thus also the serotonin metabolism (43)(44)(45). It thus seems possible that a low brain serotonin level and enhanced insulin secretion are somehow connected with the reactive hypoglycemic condition among hypoglycemic arsonists.…”
Section: )mentioning
confidence: 55%
“…Thus variations in the time courses of, and sensitivity to, induction of the three enzymes [48][49][50] are not necessarily reflected in changes in the ratios of the amino acids in the blood. These ratios, and the absolute concentrations of the amino acids, are important determinants in the synthesis of biogenic amines in the brain [23][24][25], and it has been suggested that changes in the activities of the three liver enzymes may indirectly affect neurotransmitter synthesis through effects on removal of the amino acids from the blood [51,52]. Although changes in enzyme activity may indeed be of some significance, it now seems not improbable that competition for transport into the liver cell as well as into the brain [53,54] may be of equal importance.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of the three aromatic amino acids in the blood and their ratios are important factors for neurotransmitter synthesis in the brain [23][24][25]. The activities of tryptophan 2,3-dioxygenase, phenylalanine hydroxylase and tyrosine aminotransferase change as the physiological and nutritional status changes, but not always in the same way and in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…In 1976, Cohen and Wurtman showed that dietary intake of choline for 3 to 11 days increases choline levels in the serum and acetylcholine levels in the brain of adult rats. The majority of studies could confirm these results (Ulus et al, 1978;Haubrich and Pflueger, 1979;Fernstrom, 1981;Domino et al, 1983) and only few experiments failed to register an increased brain acetyicholine content after exogenous choline administration (Eckernas, 1977;Flentge and van den Berg, 1979). Exogenous choline administration resulted in an increased ability of cholinergic neurons to synthesize acetyicholine, especially under conditions of increased neuronal demand (Schmidt and Wecker, 1981;Trommer et al, 1982).…”
Section: Discussionmentioning
confidence: 95%